Spraying Light: Ambient‐Air Fabrication of Large‐Area Emissive Devices on Complex‐Shaped Surfaces. (15th May 2014) - Sandström, Andreas; Asadpoordarvish, Amir; Enevold, Jenny; Edman, Ludvig
<x xml:space="preserve">Abstract</x> Light‐emitting electrochemical cells, featuring uniform and efficient light emission over areas of 200 cm2, are fabricated under ambient air with a for‐the‐purpose developed "spray‐sintering" process. This fault‐tolerant fabrication technique can also produce multicolored emission patterns via sequential deposition of different inks based on identical solvents. Significantly, additive spray‐sintering using a mobile airbrush allows a straightforward addition of emissive function onto a wide variety of complex‐shaped surfaces, as exemplified by the realization of a light‐emitting kitchenware fork. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>